(untitled) (Latakia University Journal -Biological Sciences Series, 2014)
أجريت تجربة ضمن ظروف منطقة الاستقرار الثانية في محطة بحوث صربايا في حلب, التابعة للهيئة العامة للبحوث العلمية الزراعية في سوريا خلال الموسم 2011-2012. هدف البحث إلى تقييم استجابة أصناف مختلفة من العدس للري التكميلي. صممت التجربة بطريقة القطع المنشقة بثلاثة مكررات, حيث تم تطبيق معاملتين مائيتين, معاملة للري التكميلي (R) ومعاملة بدون ري تكميلي (R0) على 3 أصناف من العدس هي: إدلب1 (D1) وإدلب2 (D2) وإدلب3 (D3). أظهرت النتائج تفوق R على R0 معنوياً عند مستوى ثقة 5% من حيث الانتاجية من البذور والقش ووزن ال100 بذرة, وكانت الفروقات معنوية عند تطبيق R0 حيث كان الصنف الأعلى معنوياً D3 من حيث الانتاجية من البذور والانتاجية من القش وD2 في مجال وزن ال100 بذرة. أما عند تطبيق R فقد كانت الفروقات معنوية من حيث الانتاجية من البذور (الصنف الأعلى معنوياً D3) ووزن ال100 بذرة (الصنف الأعلى معنوياً D2), بينما لم يكن هناك فروقات معنوية من حيث القش. لم يكن هناك تفاعل بين المعاملة المائية والصنف من حيث الانتاجية من البذور ووزن ال100 بذرة بينما كان هناك تفاعل من حيث القش. A study was carried out in the 2nd agro-ecological zone at the General Commission for Scientific Agricultural Research/Sirbaya Research Station/Aleppo during the growing season 2011-2012. The study aimed at evaluating the response of different varieties of lentil to supplemental irrigation. The experiment adopted a split plot design with three replicates. Two water treatments, supplemental irrigation (R) and rain feed (Ro) were applied to three varieties of lentil: IDLEB1 (D1), IDLEB1 (D2), and IDLEB1 (D3). The results showed that R was more significant than Ro at a confidence level 5% for grain, hay yield, and 100-grain weight. The differences were significant between the varieties that applied Ro; the most significant of which was D3 for grain and hay yield, and D2 for 100-grain weight. As for R, the differences were significant for grain yield (the most significant was D3) and 100-grain weight (the most significant was D2), while there was no significant difference for hay yield. There was no interaction between water treatment and the variety in terms of grain yield and 100-grain weight, while it was observed for hay yield.